2010
DOI: 10.1124/jpet.109.163253
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Influence of Protease-Activated Receptor 2 and E-Prostanoid Receptor Stimulants in Lipopolysaccharide Models of Acute Airway Inflammation

Abstract: Protease-activated receptors (PARs) are widely expressed throughout the respiratory tract, and PAR 2 has been investigated as a potential drug target for inflammatory airway diseases. The primary focus of this study was to determine the extent to which PAR 2 -activating peptides modulate lipopolysaccharide (LPS)-induced airway neutrophilia in mice and establish the underlying mechanisms. Intranasal administration of LPS induced dose-and time-dependent increases in the number of neutrophils recovered from bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…A number of PGE 2 -specific receptors have been identified, including EP1, EP2, EP3, and EP4 [17, 18], and it has been reported that macrophages can express both EP2 and EP4 [19]. To determine which receptors are involved in the apoptotic cell-induced PGE 2 signaling pathway, RAW 264.7 cells were pretreated with the EP2 receptor antagonist AH-6809 or the EP4 receptor antagonist GW-627368X for 1 h before apoptotic cells were added.…”
Section: Resultsmentioning
confidence: 99%
“…A number of PGE 2 -specific receptors have been identified, including EP1, EP2, EP3, and EP4 [17, 18], and it has been reported that macrophages can express both EP2 and EP4 [19]. To determine which receptors are involved in the apoptotic cell-induced PGE 2 signaling pathway, RAW 264.7 cells were pretreated with the EP2 receptor antagonist AH-6809 or the EP4 receptor antagonist GW-627368X for 1 h before apoptotic cells were added.…”
Section: Resultsmentioning
confidence: 99%
“…LPS was dissolved in sterile saline and administered as a single dose of 3 μg/40 μL/mouse after light anesthesia [15]. The mice were studied at the age of 13 weeks, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…[12], the selective PGE 2 receptor EP2 antagonist AH6809 (5 mg/kg, i.p.) [17], or the selective c-Met inhibitor PHA-665752 (25 mg/kg, i.p.) [11] was administrated at the same time as instillation of 10 ϫ 10 6 apoptotic Jurkat cells into bleomycin-stimulated lungs (2 days), and mice were killed 2 h later.…”
Section: Animal Protocolsmentioning
confidence: 99%